Koewolucja w systemach gospodarczych - wybrane problemy - Rzońca, Waldemar; Brol, Marian W. (Coevolution in economic systems - chosen problems, 2006)
In the paper attention was paid to the phenomenon of co-evolution in economic systems. The co-evolution in micro-scale as well as in macro-scale are characterized and the classification of macro-coevolutionary systems is presented. Moreover chosen conceptual models of co-evolution are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 149-155